2(4f+2g)2=2f(4+2g)

Simple and best practice solution for 2(4f+2g)2=2f(4+2g) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(4f+2g)2=2f(4+2g) equation:


Simplifying
2(4f + 2g) * 2 = 2f(4 + 2g)

Reorder the terms for easier multiplication:
2 * 2(4f + 2g) = 2f(4 + 2g)

Multiply 2 * 2
4(4f + 2g) = 2f(4 + 2g)
(4f * 4 + 2g * 4) = 2f(4 + 2g)
(16f + 8g) = 2f(4 + 2g)
16f + 8g = (4 * 2f + 2g * 2f)
16f + 8g = (8f + 4fg)

Solving
16f + 8g = 8f + 4fg

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-8f' to each side of the equation.
16f + -8f + 8g = 8f + -8f + 4fg

Combine like terms: 16f + -8f = 8f
8f + 8g = 8f + -8f + 4fg

Combine like terms: 8f + -8f = 0
8f + 8g = 0 + 4fg
8f + 8g = 4fg

Add '-4fg' to each side of the equation.
8f + -4fg + 8g = 4fg + -4fg

Combine like terms: 4fg + -4fg = 0
8f + -4fg + 8g = 0

Add '-8g' to each side of the equation.
8f + -4fg + 8g + -8g = 0 + -8g

Combine like terms: 8g + -8g = 0
8f + -4fg + 0 = 0 + -8g
8f + -4fg = 0 + -8g
Remove the zero:
8f + -4fg = -8g

Combine like terms: -8g + 8g = 0
8f + -4fg + 8g = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(2f + -1fg + 2g) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(2f + -1fg + 2g)' equal to zero and attempt to solve: Simplifying 2f + -1fg + 2g = 0 Solving 2f + -1fg + 2g = 0 Move all terms containing f to the left, all other terms to the right. Add '-2g' to each side of the equation. 2f + -1fg + 2g + -2g = 0 + -2g Combine like terms: 2g + -2g = 0 2f + -1fg + 0 = 0 + -2g 2f + -1fg = 0 + -2g Remove the zero: 2f + -1fg = -2g The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 3=3tx-5x | | cos(x)+cos(3x)=2sen(6x)cos(x) | | -4=-2(8x-12) | | 3=3t*-5x | | cos(x)+cos(3x)= | | Y-14=4(x-2) | | b=(3.14)(12)2 | | 5x*5x-15x-50=0 | | s*5-22=98 | | 5w-11=89 | | 9x-2=5x+8 | | 5x-10xy=5(x-2y) | | 5x-4=10y | | 2x+9=5x+54 | | 2x+15=x+16 | | 5/9+2/9= | | -6-2(m+4)=36 | | 3y-11=2y-6 | | 4x-5(2x+1)=7x+3(4x-5) | | 3/2-2/7= | | x+x+x+2=3+2x | | 4.9-5.2=4.7 | | x+x+x+2=3x+2 | | 0=80x-x | | 7x-6=3x+54 | | 4d+6+2d=6(d+6) | | -6x-12+8x-21=-6 | | x*1.012048193=84 | | -3x+11+5x+17=4 | | (4x-5)(2x+1)=0 | | 2(3d+3)=4d+6+2d | | 84y-1*y=84 |

Equations solver categories